STRATEGI PENGEMBANGAN BISNIS GLARESSA FASHION DENGAN METODE SWOT DAN BUSINESS MODEL CANVAS - Sindi Rahmayanti; Reza Widhar Pahlevi (Widya Dharma Journal of Business - WIJoB, 2025)
The objective of this research is to analyze and develop a business model, as well as to createa comprehensive businessplan for Glaressa Fashion. Glaressa fashion enterprise that provides square voal hijabs made from polyester fiber. Established in 2023, Glaressa employs qualitative research methods with a SWOT analysis and Business Model Canvas (BMC) approach. Through qualitative methods, this study collects data from interviews and observations to evaluate the strenghs, weaknesses, opportunities, and threats faced by Glaressa Fashion. By leveraging, the findings of this research can provide an effective and efficient guide for the growth and sustainability of the business